'Seeing is Believing'; the use of novel imaging approaches towards creating a greater understanding of parasite: host interactions. (4th September 2013) - Mountford, A. P.
Summary: This editorial highlights some of the key points made in the six invited reviews in this special issue of Parasite Immunology on the use of contemporary imaging technologies to investigate the parasite: host interface. Three of the reviews deal with the protozoa Trypanosoma, Leishmania, and Plasmodium, whilst the remainder focus on helminth parasites particularly Schistosoma. The reviews cover aspects related to how the development of transgenic parasites has vastly advanced our understanding of how parasites interact with host cells, particularly as a cause of pathology. Imaging technologies have also been exploited in revealing parasite localisation within host tissues and identifying novel therapeutic targets. Combined the reviews show how 'state of the art' imaging technologies have resulted in a seismic advance in our understanding of parasite biology and how this has the potential to develop new, and improved, strategies to combat disease caused by parasite infections.